Operating Decisions and the Disclosure of Management Accounting Information - Lanen, William N.; Verrecchia, Robert E. (Journal of Accounting Research, 1987)
William N. Lanen, Robert E. Verrecchia, Operating Decisions and the Disclosure of Management Accounting Information, Journal of Accounting Research, Vol. 25, Studies on Stewardship Uses of Accounting Information (1987), pp. 165-189